The longevity legacy: the problem of old animals in zoos - Kitchener, Andrew; Macdonald, Alastair A (Blackwells, 2002)
Zoos once demonstrated their skill in keeping wild mammals in captivity by longevity records. However, as our knowledge of animal husbandry in zoos has increased and breeding in most species has become commonplace, so the emphasis has shifted to continued breeding success and the management of sustainable zoo populations. There has also been undoubtedly an increase in the maximum and mean longevities of most species. For example, in a period of 30 years, the maximum longevities of gorillas (Gorilla sp.) increased by 62% to 54 years, that of orung utans (Pongo sp.) by 92% to 59 years, pygmy marmosets (Callithrix pygmaea) by 267% to 17.9 years and Goeldi's monkeys (Callimico goeldii) by 678% to 18 years (Jones, 1962; Nowak, 1999). Over the last 10 years or so the National Museums of Scotland have been collecting dead animal specimens from many zoos in order to provide a research resource and to provide a number of specimens for educational displays. As a consequence it has come to our notice that many of the large mammals are commonly suffering from a variety of skeletal and dental pathologies. This was most noticeable in bears, of which more than 96% have skeletal pathologies at the age of 15 years or greater (Kitchener, 2004; Kitchener et al., 2001). In this paper, we expand the range of species in order to determine how widespread these problems are and to see if there are any significant interspecific differences that might be influenced by species-specific behaviour, environment and morphology.
Keywords: zoo; animal husbandry; longevity; dental pathology; skeletal pathology